PENGARUH PENERAPAN KECAKAPAN HIDUP (LIFE SKILLS) DAN TINGKAT KECAKAPAN HIDUP TERHADAP PENGAMBILAN KEPUTUSAN PROFESI :Studi Kasus Pada Siswa Kelas XII di Sekolah Menengah Kejuruan Negeri 12 Bandung Tahun Ajaran 2008/2009 - Ignatius, Slamet (2012)
This study is conducted at SMKN 12 Bandung to find out the influence of life skills implementation level and students life skills level towards students' ability in taking decision on certain profession. The first hypothesis is that there is any positive influence of life skills implementation towards students' ability in taking decision on certain profession. The second is that there is any positive influence of level of life skills towards students' ability in taking decision on certain profession. The third is that there is any positive influence of life skills implementation and level of life skills towards students' ability in taking decision on certain profession. Respondens for this study involved the population of 196 students in the final semester in all diciplines available in school, 125 of which were chosen randomly. By using Likert Scale Model questionares, the evaluations are based on the perception of respondents towards life skills implementation, their life skills level and their ability to take decision on certain profession. The collected data were then analyzed by using analitic-descriptive approach of data normality test. While infferential-statistics approach of simple regression & correlation and multiple regression & correlation were used to test the hypotheses. The findings show (1) that the level of life skills implementation was perceieved by students to be at a high level. It is described further that 17% of students perceived at a moderate level, 64% high dan 19% very high.. Students perceived that their life skills is at a high level. It is described further that 2% of students perceived at a low level, 31% moderate, 61% high, dan 6% very high. Students perceived that they have high ability in taking decision on certain proffesion. It is described further that 1% of students perceieved to have low ability, 30% moderate, 55% high and 4% very high; (2) that there is any positive influence of life skills implementation towards students' ability in taking decision on certain profession (20,25%) and level of life skills (27%) towards students' ability in taking decision on certain profession; (3) that there is any positive influence of life skills implementation and level of life skills towards students' ability in taking decision on certain profession (38,4%). It is suggested that the school should check its curriculum design on how to implement life skills in a better way. Students should fully understand the important dimension of life skills needed in industries, learn how to improve their life skills, get involved more in extracurricular activities, and be more active in teaching and learning activities. Further study needs to involve more respondents from different schools and different diciplines to get more complete description which can support this study. Further study is also suggested to examine other independent variables which may influence dependent variable.